Mismatch repair genes in Lynch syndrome: a review - Silva, Felipe Cavalcanti Carneiro da; Valentin, Mev Dominguez; Ferreira, Fábio de Oliveira; Carraro, Dirce Maria; Rossi, Benedito Mauro (São Paulo Medical Journal, 2009)
Lynch syndrome represents 1-7% of all cases of colorectal cancer and is an autosomal-dominant inherited cancer predisposition syndrome caused by germline mutations in deoxyribonucleic acid (DNA) mismatch repair genes. Since the discovery of the major human genes with DNA mismatch repair function, mutations in five of them have been correlated with susceptibility to Lynch syndrome: mutS homolog 2 (MSH2); mutL homolog 1 (MLH1); mutS homolog 6 (MSH6); postmeiotic segregation increased 2 (PMS2); and postmeiotic segregation increased 1 (PMS1). It has been proposed that one additional mismatch repair gene, mutL homolog 3 (MLH3), also plays a role in Lynch syndrome predisposition, but the clinical significance of mutations in this gene is less clear. According to the InSiGHT database (International Society for Gastrointestinal Hereditary Tumors), approximately 500 different LSassociated mismatch repair gene mutations are known, primarily involving MLH1 (50%) and MSH2 (40%), while others account for 10%. Much progress has been made in understanding the molecular basis of Lynch Syndrome. Molecular characterization will be the most accurate way of defining Lynch syndrome and will provide predictive information of greater accuracy regarding the risks of colon and extracolonic cancer and enable optimal cancer surveillance regimens.